Pelanggaran Etika Pariwara Indonesia pada Iklan Komersial K Natural White dan Buavita di Global TV - Afiannur, Restu Rizqy; Musa, Ivan Wisnu; Firmansyah, Riffat; Junaedi, Fajar (Jurnal Audiens, 2025)
This study aims to analyze violations of the Indonesian Advertising Ethics (EPI) in the advertisements of K Natural White and Buavita products broadcast on television. This research employs a descriptive qualitative method using observation and documentation approaches to identify and analyze advertising content that breaches ethical principles. The findings reveal that the K Natural White advertisement violates the EPI clause on honesty due to claims such as "anti-aging" and "rich in natural antioxidants" that lack valid scientific evidence, while the statement "dermatologically tested" requires further transparency. Meanwhile, the Buavita advertisement breaches the same principle with claims like "100% vitamin C" and "pure fruit," which are inconsistent with the product's actual composition. These findings indicate that EPI violations in advertisements can influence consumer perceptions and create unrealistic expectations. Therefore, compliance with the Indonesian Advertising Ethics is essential to maintain consumer trust and protection.